2007
DOI: 10.1002/jgt.20240
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between total domination, order, size, and maximum degree of graphs

Abstract: A total dominating set, S, in a graph, G, has the property that every vertex in G is adjacent to a vertex in S. The total dominating number, γt(G) of a graph G is the size of a minimum total dominating set in G. Let G be a graph with no component of size one or two and with Δ(G) ≥ 3. In 6, it was shown that |E(G)| ≤ Δ(G) (|V(G)|–γt(G)) and conjectured that |E(G)| ≤ (Δ(G)+3) (|V(G)|–γt(G))/2 holds. In this article, we prove that $\leq (\Delta(G)+ 2\sqrt{\Delta}) (|V(G)| - \gamma_{t}(G))/2$ holds and that the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The best-known lower and upper bounds (before this paper) to date on c Δ and r Δ for every ≥ Δ 3 are given by Rautenbach [18] and Yeo [24], and are summarized below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-known lower and upper bounds (before this paper) to date on c Δ and r Δ for every ≥ Δ 3 are given by Rautenbach [18] and Yeo [24], and are summarized below.…”
Section: Introductionmentioning
confidence: 99%
“…As remarked by Yeo [24], "we do not have a guess if r Δ actually grows proportionally with ln(Δ) or Δ or some completely different function. "…”
Section: Introductionmentioning
confidence: 99%
“…A domination set D of a graph G is called a total dominating set if G[D] has no isolated vertex, and the minimum cardinality of a total dominating set in G is called the total domination number of G, denoted by γ t (G). Total domination in graphs was introduced by Cockayne, Dawes, and Hedetniemi [6], and has been well studied (see, for example, [8,9,17,28]).…”
Section: Introductionmentioning
confidence: 99%
“…Sanchis [15] showed that if we restrict our attention to connected graphs with total domination number at least 5, then the bound in [4] can be improved slightly. The square dependence on n and γ t presented in [4,15] is improved in [9,16,19] into a linear dependence on n, γ t and ∆ by demanding a more even distribution of the edges by restricting the maximum degree ∆. In particular, the following linear Vizing-like relation relating the size of a graph and its order, total domination number, and maximum degree is established in [9,16].…”
Section: Introductionmentioning
confidence: 99%